Researching Communications : a practical guide to methods in media and cultural analysis - Deacon, David (New York : Bloomsbury Academic, 2021)
"The new edition of the highly respected Researching Communications is a comprehensive and authoritative guide to researching media and communication. Researching Communications, Third Edition is an invaluable guide to performing and analysing research tasks, introducing the major research methods, giving detailed examples of research analysis and practical step-by-step guidance in clear language. Written by highly regarded experts in the field, the third edition includes new sections on social media analysis, digital research methods and comparative research, as well as updated case studies, international examples and details of recent developments in media and communication studies. Undergraduate and postgraduate media and communication students will find Researching Communications an invaluable resource at all stages of their course"--
Approaching research : communications and contemporary life -- Dealing with documentation -- Selecting and sampling -- Asking questions -- Handling numbers -- Counting contents -- Analysing texts -- Unpacking news -- Viewing the image -- Interpreting images -- Being an observer -- Attending to talk -- Taking talk apart -- Making comparisons -- Using computers -- Beyond methodology : the what, how and why of researching communications.
Includes bibliographical references and index.
Keywords: Communication -- Research -- Methodology; Mass media -- Research -- Methodology; Communication and culture; Mass media and culture